Konstribusi Model Pendidikan Pondok Pesantren Darunnajah Kabupaten Banyuwangi dalam Peningkatan Sumberdaya Manusia: The Contribution of the Darunnajah Islamic Boarding School Education Model in Banyuwangi Regency to Human Resource Development - M. Syamsudini (Fenomena, 2017)
The limited capacity of traditional Islamic boarding schools (pesantren) to respond to modernization and produce competitive human resources remains a critical issue in contemporary Indonesian education. This study addresses the broad problem of how pesantren can reform their educational models to enhance human resource quality, particularly in the era of regional autonomy. The research specifically aims to examine the educational model developed by Darunnajah Islamic Boarding School in Banyuwangi and its contribution to improving human resources. A qualitative approach was employed, utilizing observation, in-depth interviews with kyai, teachers, and students, and documentary studies to collect data. The findings reveal that Darunnajah develops three integrated educational models: traditional (salaf), modern (kholaf), and comprehensive, which combines classical Islamic kitab learning with formal education, computer and science laboratories, a modern library, and an innovative Islamic Nasyid arts school. These models aim to produce graduates who are not only proficient in religious knowledge but also possess general academic skills and artistic talents. The study concludes that the integration of traditional and modern systems significantly supports human resource development. It is recommended that pesantren foundations improve facilities and coordination, while teachers and students optimize time management and actively participate in extracurricular activities to maximize competency. Keterbatasan pesantren tradisional dalam merespons modernisasi dan menghasilkan sumber daya manusia yang kompetitif merupakan isu krusial dalam pendidikan Indonesia kontemporer. Penelitian ini membahas peta besar masalah bagaimana pesantren dapat mereformulasi model pendidikannya untuk meningkatkan kualitas sumber daya manusia, khususnya di era otonomi daerah. Tujuan penelitian adalah mengkaji model pendidikan yang dikembangkan Pondok Pesantren Darunnajah di Banyuwangi serta kontribusinya terhadap peningkatan sumber daya manusia. Penelitian menggunakan pendekatan kualitatif dengan teknik observasi, wawancara mendalam terhadap kiai, ustadz, dan santri, serta studi dokumentasi. Hasil penelitian menunjukkan bahwa Darunnajah mengembangkan tiga model pendidikan terintegrasi: tradisional (salaf), modern (kholaf), dan komprehensif, yang memadukan pengajaran kitab kuning dengan pendidikan formal, laboratorium komputer dan IPA, perpustakaan modern, serta sekolah seni Nasyid Islami. Model-model ini bertujuan melahirkan lulusan yang unggul dalam pengetahuan agama, akademik umum, dan keterampilan seni. Kesimpulannya, integrasi sistem tradisional dan modern berkontribusi signifikan terhadap pengembangan sumber daya manusia. Direkomendasikan agar pengurus yayasan meningkatkan sarana prasarana, serta ustadz dan santri mengoptimalkan waktu dan kegiatan ekstrakurikuler untuk memperkuat kompetensi lulusan.